The effects of elemene emulsion injection on rat fecal microbiota and metabolites: Evidence from metagenomic exploration and liquid chromatography-mass spectrometry - Gu, Lei; Wu, Hao; Zhang, Yang; Wu, Yousheng; Jin, Yuan; Li, Tian; Ma, Litian; Zheng, Jin (Frontiers in Microbiology, 2022)
Objective Elemene emulsion injection (EEI) has been approved for interventional and intracavitary chemotherapy in treating malignant ascites in China, but few studies have focused on the effects of EEI on gut microbiota and metabolites. In this study, we investigated the effects of EEI on the fecal microbiota and metabolites in healthy Sprague-Dawley (SD) rats. Methods We randomly assigned 18 male SD rats to three groups (n = 6 in each group): the sham group (group S), the low-concentration EEI group (L-EEI), and the high-concentration EEI group (H-EEI). The L-EEI and H-EEI rats were administered 14 days of consecutive EEI, 20 mg/kg, and 40 mg/kg intraperitoneally (IP). Group S rats were administered the same volume of normal saline. On day 14, each animal's feces were collected for metagenomic sequencing and metabolomic analysis, and the colonic contents were collected for 16S rRNA sequencing. Results EEI could alter the β-diversity but not the α-diversity of the fecal microbiota and induce structural changes in the fecal microbiota. Different concentrations of EEI affect the fecal microbiota differently. The effects of different EEI concentrations on the top 20 bacteria with significant differences at the species level among the three groups were roughly divided into three categories: (1) A positive or negative correlation with the different EEI concentrations. The abundance of Ileibacterium Valens increased as the EEI concentration increased, while the abundance of Firmicutes bacteria and Clostridium sp. CAC: 273 decreased. (2) The microbiota showed a tendency to increase first, then decrease or decrease first, and then increase as EEI concentration increased—the abundance of Prevotella sp. PCHR, Escherichia coli, and Candidatus Amulumruptor caecigallinarius tended to decrease with L-EEI but significantly increased with H-EEI. In contrast, L-EEI significantly increased Ruminococcus bromii and Dorea sp. 5–2 abundance, and Oscillibacter sp. 1–3 abundance tended to increase, while H-EEI significantly decreased them. (3) L-EEI and H-EEI decreased the abundance of bacteria (Ruminococcaceae bacterium, Romboutsia ilealis, and Staphylococcus xylosus). Fecal metabolites, like microbiota, were sensitive to different EEI concentrations and correlated with fecal microbiota and potential biomarkers. Conclusion This study shows that intraperitoneal EEI modulates the composition of rat fecal microbiota and metabolites, particularly the gut microbiota's sensitivity to different concentrations of EEI. The impact of changes in the microbiota on human health remains unknown, particularly EEI's efficacy in treating tumors.